Surface analysis of hydrophobicity of Thai silk treated by SF6 plasma - P. Suanpoot (2018)
Hydrophobicity of Thai silk has been improved by plasma treatment using SF6gases discharged by an inductively coupled plasma (ICP). The plasma was generated under a pressure range of 1.3-40.0 Pa while the RF power input is in a range of 20-100 W. A single RF compensated Langmuir probe and optical emission spectroscopy (OES) were used for the plasma diagnostics. The mechanisms responsible for the hydrophobic behavior were evaluated by SEM, X-ray photoelectron spectroscopy (XPS), attenuated total reflection (ATR) infrared spectroscopy, and were compared with quantum mechanical calculation. ATR-IR detected slightly changes for the peak intensities of the bands located in the frequency region of 1000-1050 cm- 1. XPS analysis results show the presence of CF-CF group as the increment of C/F ratio with increasing pressures. The results also agree with the density functional calculation. A fluorine radical shows the deposition by CH + F-→ CF + H-reaction. © 2008 Elsevier B.V. All rights reserved.